WI2020 Community Tracks 2020
DOI: 10.30844/wi_2020_u1-marx
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gap between Smart Manufacturing Applications and Data Management

Abstract: Smart manufacturing refers to the intensified collaboration of machines, products, and people throughout the manufacturing and the supply chain. This facilitates innovative products, services, business models, and processes. Smart manufacturing is premised on emerging technologies such as cloud computing, mobile computing, the Internet of Things, data analytics, and artificial intelligence. A plethora of companies struggles with the implementation of corresponding applications. In research and practice, we see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Thereafter, Sundarraj et al [28] reviewed different types of data governance in the context of SF for ensuring DQ. Additionally, Emanuel et al [8] identified data management requirements on the SM implementation, including establishing DQ standards and continuous DQ check for the IS integration, based on DQ dimensions. The researchers included DQ management as a component in their proposed data management framework for SM applications.…”
Section: Related Studies On Data Quality In Smart Factorymentioning
confidence: 99%
See 3 more Smart Citations
“…Thereafter, Sundarraj et al [28] reviewed different types of data governance in the context of SF for ensuring DQ. Additionally, Emanuel et al [8] identified data management requirements on the SM implementation, including establishing DQ standards and continuous DQ check for the IS integration, based on DQ dimensions. The researchers included DQ management as a component in their proposed data management framework for SM applications.…”
Section: Related Studies On Data Quality In Smart Factorymentioning
confidence: 99%
“…We utilised eight databases as the initial resources for the search as advised by relevant review studies in this field [8,9,22,23]. The eight databases used in this review are: ACM Digital Library, ASME Digital Collection, Emerald Insight, IEEE Xplore, ScienceDirect, Scopus, Taylor & Francis Online, and Web of Science.…”
Section: Selecting Databases and Outletsmentioning
confidence: 99%
See 2 more Smart Citations